Sagradas apropriações: A mulher que escreveu a Bíblia, de Moacyr Scliar - Simone Guimaraes Matheus (2011)
This Thesis does a reading based on the novel A mulher que escreveu a Bíblia (The woman who wrote the Bible), from Moacyr Scliar. It is from a thought (reflection) about the intertextual relations between the literature and the Bible, having as a background the biblical episodes rewritten in the novel. The author rewrites some biblical episodes using irony and breaking down myths, characters and some themes (issues) from the sacred text.